局部路径规划方法、装置、计算机设备和存储介质 (2023)
本申请涉及一种局部路径规划方法、装置、计算机设备和存储介质。所述方法包括：获取参考路径；在所述参考路径的起点和终点之间，根据第一预设间隔，获取多个采样点；根据所述自行设备的位置，周期性规划两个相邻采样点之间的局部路径。本申请实施例能使局部路径的规划更加合理，使得局部路径更加平滑。 The invention relates to a local path planning method and device, computer equipment and a storage medium. The method comprises the following steps: acquiring a reference path; acquiring a plurality of sampling points between the starting point and the ending point of the reference path according to a first preset interval; and according to the position of self-propelled equipment, periodically planning a local path between two adjacent sampling points. According to the embodiment of the invention, the planning of the local path is more reasonable, and the local path is smoother.